Critical international relations and the impact agenda. Issue 3 (3rd September 2018) - Selby, Jan
Abstract How should critical international relations (IR) scholars approach the 'impact agenda'? While most have been quite resistant to it, I argue in this essay that critical IR should instead embrace the challenge of impact—and that both IR as a field and the impact agenda more broadly would gain greatly from it doing so. I make this case through three steps. I show, firstly, that critical IR has until now been very much at the impact agenda's margins, and that this situation contrasts strikingly with its well-established importance within IR teaching and research. I argue, secondly, that critical IR scholars both could and should do more impact work—that the current political conjuncture demands it, that many of the standard objections to doing so are misplaced and indeed that 'critical' modes of research are in some regards better suited than 'problem-solving' ones to generating meaningful change—and offer a series of recommended principles for undertaking critically oriented impact and engagement work. But I also argue, thirdly, that critical social science holds important lessons for the impact agenda, and that future impact assessments need to take these lessons on board—especially if critical IR scholarship is to embrace impact more fully. Critical IR, I submit, should embrace impact; but at the same time, research councils and assessments could do with modifying their approach to it, including by embracing a more critical and political understanding of what impact is and how it is achieved.